2014
DOI: 10.1371/journal.pone.0097423
|View full text |Cite|
|
Sign up to set email alerts
|

Mouse Models of Intracerebral Hemorrhage in Ventricle, Cortex, and Hippocampus by Injections of Autologous Blood or Collagenase

Abstract: Intracerebral hemorrhage (ICH) is a devastating condition. Existing preclinical ICH models focus largely on striatum but neglect other brain areas such as ventricle, cortex, and hippocampus. Clinically, however, hemorrhagic strokes do occur in these other brain regions. In this study, we established mouse hemorrhagic models that utilize stereotactic injections of autologous whole blood or collagenase to produce ventricular, cortical, and hippocampal injury. We validated and characterized these models by histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 48 publications
0
79
0
Order By: Relevance
“…At 24 hrs after ICH induction, neurological deficit scores (NDS) were determined by using a 24-point scoring system [22, 23], including body symmetry, gait, climbing, circling behavior, front limb symmetry, and compulsory circling. Each test was graded from 0 to 4, establishing a maximum deficit score of 24.…”
Section: Methodsmentioning
confidence: 99%
“…At 24 hrs after ICH induction, neurological deficit scores (NDS) were determined by using a 24-point scoring system [22, 23], including body symmetry, gait, climbing, circling behavior, front limb symmetry, and compulsory circling. Each test was graded from 0 to 4, establishing a maximum deficit score of 24.…”
Section: Methodsmentioning
confidence: 99%
“…Brain tissue loss is common in ICH models [29,32]. Histology results in previous studies showed that tissue loss and brain atrophy occured in several brain regions, including cortex [29] and striatum [37].…”
Section: Discussionmentioning
confidence: 98%
“…Each test was graded from 0 to 4, providing a total score of 0 to 24, with higher scores indicative of greater neurologic injury [29,31,32].…”
Section: Functional Assessmentmentioning
confidence: 99%
“…Coronal cryostat sections 400μm apart between bregma -0.5 mm and bregma -4.5mm were stained with hematoxylin and eosin. Image J software (NIH, Bethesda, MD, USA) was used to quantify lesion volumes (Zhu et al 2014). The volume of the lesion in cubic millimeters was calculated as the sum of the damaged areas of each section multiplied by the interslice distance (Wu et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…We compared the total time spent exploring the old and new objects. The exploration time included time in direct contact with the object and time within the object area; a discrimination index (total time spent with new object/total time devoted to exploration of objects) was also calculated for each rat (Zhu et al 2014). …”
Section: Methodsmentioning
confidence: 99%